Empowering Communities through Financial Literacy Initiatives for SME Development - Awaluddin, Sri Prilmayanti; Paula, Eka Wijaya; Tamriesfatno, Sigrid; Adijah S, Andi Adijah S; Khair, Andi Ummul (Golden Ratio of Community Services and Dedication, 2025)
Financial literacy initiatives are crucial in empowering communities for small and medium-sized enterprise (SME) development. This qualitative literature review explores the landscape of financial literacy programs targeting SMEs, their effectiveness, and the contextual factors influencing their outcomes. The research methodology systematically selects peer-reviewed articles, books, and reports published between 2012 and 2022, utilizing databases such as PubMed, Google Scholar, Web of Science, and Scopus. Data collection entails thorough reading and analysis of selected sources, followed by iterative coding to identify key themes and insights. The findings reveal a diverse range of financial literacy interventions, including workshops, training seminars, and online resources, tailored to address the specific needs of SME owners and entrepreneurs. Cultural, socio-economic, and institutional contexts significantly influence the design and implementation of these programs, highlighting the importance of contextual sensitivity. Participation in financial education programs positively impacts SMEs' financial knowledge, decision-making abilities, and business performance, leading to improved access to financing and sustainable growth. However, challenges such as resource constraints and low financial awareness hinder the scalability and effectiveness of these initiatives. Leveraging technology and innovative delivery methods, such as digital platforms and social media, holds promise in expanding the reach and impact of financial literacy programs, particularly in underserved communities. This review underscores the importance of continued investment in financial education to unlock the full potential of SMEs as drivers of economic prosperity and social progress.